Avaliação da atividade diurética de Aspidosperma subincanum Mart. e a participação de prostanoides nesta resposta - Ribeiro, Emmeline Flor (2014)
Aspidosperma subincanum Mart. is a medicinal herb used for the treatment of hypercholesterolemia, diabetes and digestive illnesses. The bitter tonic of its bark is known by the indigenous population to stimulate circulatory functions. Although a previous study showed that EEAS induces hypotension associated with bradycardia and vasodilation, no scientific data have been described to evaluate the diuretic effects of this Brazilian medicine plant. The aim of the present study was to evaluate the diuretic activity of an ethanol extract of Aspidosperma subincanum (EEAS), and possible mechanisms of action, using Wistar rats. EEAS, 60, 120 and 300 mg/Kg, or furosemide (20 mg/Kg) were orally administered and the rats were kept individually in metabolic cages for 24h for urine collection 1, 2, 4, 6, 8, 12 and 24h after treatments. To evaluate the involvement of prostanoids in the diuretic action of EEAS, the animals received piroxicam (5 mg/Kg, i.p.), a nonselective inhibitor of cyclooxygenase, before treatment with EEAS 120 mg/Kg. The control groups received only saline (NaCl, 0,9%), or saline and piroxicam. The urinary volume, the water consumption, electrolyte excretion and pH were measured. The oral administration of EEAS 60 and 120mg/Kg increased significantly the urine and electrolyte excretion of Na+ and K+ continuously throughout the study period, wherein increased the urinary output from the first hour after treatment, and increased the electrolytes from the second hour onwards after treatment. EEAS 60 and 120 mg/Kg caused a relative increase in cumulative diuresis around of 77% and 142,95%, respectively, compared with the control group. EEAS 300 mg/Kg increased the urinary excretion from 8 h after treatment. From 4 h until the end of the experiment, the group treated with EEAS 120 mg/kg provided a major excretion of Na+ than the furosemide group, while the group treated with EEAS 60 mg/Kg provided a similar excretion of Na+ when compared to the group that received furosemide. The furosemide group showed significantly higher amounts of K+ in the urine when compared with the others group. The urinary excretion of EEAS was reduced by piroxicam 2 h, 4 h and 8 h after treatments by around 54.2%, 50.3% and 38.9%, respectively. Piroxicam reduced Na+ excretion between 4 and 8 h after treatments by 38.4 and 39.0%, respectively. And still inhibited the K+ excretion by around 28.2% at 4 h and 47.1% at 8 h. The results suggest that EEAS could present compound(s) responsible for diuretic activities, and the mechanism could involve prostanoids system.